Tetralogy of Fallot Repair in Developing Countries: International Quality Improvement Collaborative (2018)
Background: Isolated reports from low- and middle-income countries (LMICs) for surgical results in tetralogy of Fallot (TOF) are available. The International Quality Improvement Collaborative for Congenital Heart Disease (IQIC) seeks to improve surgical results promoting reductions in infection and mortality in LMICs. Methods: All cases of TOF in the IQIC database performed between 2010 and 2014 at 32 centers in 20 LMICs were included. Excluded from the analysis were TOF with any associated lesions. A logistic regression analysis was performed to identify risk factors for in-hospital mortality after surgery for TOF. Results: A total of 2,164 patients were identified. There were 1,839 initial primary repairs, 200 with initial systemic-to-pulmonary artery shunt, and 125 underwent secondary repair after initial palliation. Overall mortality was 3.6% (78 of 2,164), initial primary repair was 3.3% (60 of 1,839), initial systemic-to-pulmonary artery shunt was 8.0% (16 of 200), and secondary repair was 1.6% (2 of 125; p = 0.003). Major infections occurred in 5.9% (128 of 2,164) of the entire cohort. Risk factors for death after the initial primary repair were oxygen saturation less than 90% and weight/body mass index for age below the fifth percentile (p less than 0.001). The initial primary repair occurred after age 1 year in 54% (991 of 1,839). Older age at initial primary repair was not a risk factor for death (p = 0.21). Conclusions: TOF patients are often operated on after age 1 year in LMICs. Unlike in developed countries, older age is not a risk factor for death. Nutritional and hypoxemic status were associated with higher mortality and infection. This information fills a critical knowledge gap for surgery in LMIC. © 2018 The Society of Thoracic Surgeons